2020
DOI: 10.3390/ijms21124568
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Breast Cancer Margins by Tissue Spray Mass Spectrometry

Abstract: Current methods for the intraoperative determination of breast cancer margins commonly suffer from the insufficient accuracy, specificity and/or low speed of analysis, increasing the time and cost of operation as well the risk of cancer recurrence. The purpose of this study is to develop a method for the rapid and accurate determination of breast cancer margins using direct molecular profiling by mass spectrometry (MS). Direct molecular fingerprinting of tiny pieces of breast tissue (approximately 1 × 1 × 1 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…The following lipidome data collections (DC) were used in this study 22–24 : (1) blood plasma samples from patients with/without endometriosis (36/24 samples); (2) blood plasma samples from patient with first‐case myoma/recurrent myoma/control (40/59/26 samples); (3) breast tissue samples from patient with breast cancer and with/without lymph node metastasis (48/38 samples); (4) breast cancer tissue samples from patient with/without lymph node metastasis (48/40 samples); (5) cervical tissue samples with/without neoplastic lesions (33/25 samples). DC1–DC4 were obtained by reversed phase liquid chromatography‐mass spectrometry analysis of lipid extract with identification of lipids by Lipid Match scripts 25 .…”
Section: Methodsmentioning
confidence: 99%
“…The following lipidome data collections (DC) were used in this study 22–24 : (1) blood plasma samples from patients with/without endometriosis (36/24 samples); (2) blood plasma samples from patient with first‐case myoma/recurrent myoma/control (40/59/26 samples); (3) breast tissue samples from patient with breast cancer and with/without lymph node metastasis (48/38 samples); (4) breast cancer tissue samples from patient with/without lymph node metastasis (48/40 samples); (5) cervical tissue samples with/without neoplastic lesions (33/25 samples). DC1–DC4 were obtained by reversed phase liquid chromatography‐mass spectrometry analysis of lipid extract with identification of lipids by Lipid Match scripts 25 .…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the ROC results were in agreement with PCA, meaning that PCs and TGs can be putative biomarkers for BC diagnosis. Another study obtained significant differences ( p < 0.05) in lipid levels between BC and normal tissues using tissue spray mass spectrometry, for PI, PCs, and SM [ 98 ]. Moreover, the results obtained by orthogonal partial least-squares discriminant analysis (OPLS-DA) classification of the tissue revealed 100% sensitivity and specificity when compared to histological analysis [ 98 ].…”
Section: Breast Cancer Lipidomics—in Tissue Approachmentioning
confidence: 99%
“…Another study obtained significant differences ( p < 0.05) in lipid levels between BC and normal tissues using tissue spray mass spectrometry, for PI, PCs, and SM [ 98 ]. Moreover, the results obtained by orthogonal partial least-squares discriminant analysis (OPLS-DA) classification of the tissue revealed 100% sensitivity and specificity when compared to histological analysis [ 98 ]. Finally, Cifková et al [ 19 ] correlated the lipidomic profile of cell lines and tissues of BC patients using HILIC/ESI-MS combined with multivariate data analysis (e.g., PCA, OPLS-DA).…”
Section: Breast Cancer Lipidomics—in Tissue Approachmentioning
confidence: 99%
“…Shotgun lipidomics based on electrospray ionization mass spectrometry (ESI-MS) allows deep molecular profiling of a sample without significant losses of chemical information [26,27]. The high diagnostic potential of lipidomics has been shown in many areas of medicine, particularly in oncology: lung, thyroid gland, breast, stomach, pancreas, colorectal, liver, kidney, prostate, ovarian, and endometrium cancer [28,29,[38][39][40][41][42][43][44][45][46][47]30,[48][49][50][51][31][32][33][34][35][36][37]. MS studies of lipid profiles in tissues and blood plasma have revealed new promising biomarkers of endometriosis (benign gynecological disorder) [26,27,32,33,37,44,47].…”
Section: Introductionmentioning
confidence: 99%